Ethanol extractives of fossil Sequoia wood - Uçar, G; Balaban, M; Gören, N (SPRINGER, 1998)
Except for small amounts of neutral compounds, the ethanol extracts from fossil Sequoia wood contained over 80% polymeric substances. The bulk of materials was separated into fractions by column chromatography and investigated by means of UV- and FTIR spectroscopy. According to the results the polymeric products are a type of Brauns lignins. Both spectroscopic data revealed considerable changes in composition and constitution of Lignin.
Keywords: LIGNINS; SPECTROSCOPY; Materials Science